2013
DOI: 10.1139/cjfas-2013-0116
|View full text |Cite
|
Sign up to set email alerts
|

Classification of hatchery and wild fish using natural geochemical signatures in otoliths, fin rays, and scales of an endangered catostomid

Abstract: Endangered and endemic June sucker (JS, Chasmistes liorus) have been stocked for many years to prevent extinction in Utah Lake, Utah. When unmarked fish appeared in the lake at higher rates than expected from tag loss, we sought to determine if 87 Sr/ 86 Sr and Sr/Ca (signatures) in otoliths, fin rays, and scales could be used to identify whether stocking had created a naturally reproducing population. Signatures from otoliths and fin rays suggested that approximately 38% (12 of 31) of unmarked JS probably cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Three known-stocked individuals were not classified as being of JWFH origin, although the Sr:Ca values of the first 5 lm of the laser-ablation transect near the fin ray core for each of these individuals were within the range of the JWFH Sr:Ca signature. Nevertheless, the results of this study are consistent with previous investigations, which demonstrated that otolith Sr:Ca (and other naturally-occurring markers) can be used to identify hatchery-reared individuals with a high degree of accuracy in populations consisting of hatchery-origin and wild fish (Bickford & Hannigan 2005;Zitek et al 2010;Wolff et al 2013). More thorough sampling of the fin ray core with a pattern of laser-ablated spots or a raster would likely increase the probability of detecting the hatchery Sr:Ca signature in the fin ray core.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Three known-stocked individuals were not classified as being of JWFH origin, although the Sr:Ca values of the first 5 lm of the laser-ablation transect near the fin ray core for each of these individuals were within the range of the JWFH Sr:Ca signature. Nevertheless, the results of this study are consistent with previous investigations, which demonstrated that otolith Sr:Ca (and other naturally-occurring markers) can be used to identify hatchery-reared individuals with a high degree of accuracy in populations consisting of hatchery-origin and wild fish (Bickford & Hannigan 2005;Zitek et al 2010;Wolff et al 2013). More thorough sampling of the fin ray core with a pattern of laser-ablated spots or a raster would likely increase the probability of detecting the hatchery Sr:Ca signature in the fin ray core.…”
Section: Discussionsupporting
confidence: 91%
“…Clarke et al 2007;Allen et al 2009;Smith & Whitledge 2011;Phelps et al 2012;Wolff et al 2013;Woodcock et al 2013), although these are not perfectly matrix-matched with fin rays. Pelvic fin ray sections were prepared for analysis of Sr:Ca under a class 100 laminar flow hood and handled with non-metallic acid-washed forceps.…”
Section: Methodsmentioning
confidence: 99%
“…The relative importance of water and dietary sources to the otoliths may change depending on Ca availability in the water column; as Ca concentration varies with salinity, freshwater fish may compensate for decreased water-Ca by deriving more ions from their food. There are also two studies carried out by an American team: the first [137] concerned the use of the 87 Sr/ 86 Sr isotopic ratios in fish otoliths to determine the origins of invasive piscivores in the Upper Colorado River Basin (UCRB, western USA); the second study [138] was carried out to determine whether 87 Sr/ 86 Sr and Sr/Ca signatures in otoliths, fin rays and scales of June sucker (JS, C. liorus) could be used to identify whether the stocking carried out for many years previously to prevent fish extinction in Utah Lake (USA) had created a naturally reproducing population. In the first study, fish were collected during 2004-2009 from reservoirs and rivers throughout the basin.…”
Section: Fish Productsmentioning
confidence: 99%
“…As such, variation in elemental concentrations in the ambient environment alters the deposition of elemental signatures in hard structures, resulting in a biological tag (Wolff et al. ). Natural differences in ambient water chemistry reflected in the elemental signatures that accumulated in otoliths and fin rays during hatchery rearing were used to successfully identify the origin of known hatchery‐reared Muskellunge Esox masquinongy (Rude et al.…”
mentioning
confidence: 99%
“…) and unmarked hatchery‐ and wild‐reared June Sucker Chasmistes liorus (Wolff et al. ). Alternatively, stable isotope marking involves deliberately manipulating the natural isotopic ratio of particular elements (e.g., 88 Sr/ 86 Sr and 138 Ba/ 137 Ba), which typically show little variation in the natural environment, to intentionally induce an elemental mark (MacLellan and Fargo ; Thorrold et al.…”
mentioning
confidence: 99%